BEST PRACTICE IN TEACHING ENGLISH GRAMMAR TO UNIVERSITY STUDENTS: DEDUCTIVE, INDUCTIVE, OR COMBINATION OF BOTH? - Wisma Yunita (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Universities preparing future English teachers in Indonesia usually put English grammar courses in their curricula. The courses are usually given at the first to the fourth semester and with wide material coverage. Some made it discrete in a course. Some made it integrated with skills of English language. Grammar as a part of language knowledge should be mastered well by students at university especially the future English teachers. Future English teachers who have lack of English grammar knowledge will face difficulties in performing English in spoken and written. Therefore, they should be taught using an appropriate approach of English grammar teaching so that they will have a thorough mastery of the grammar. In contrary, the students should also give more effort in mastering the grammar by reading more materials related to grammar and practicing the rules in spoken and written. Currently, there are two major approaches widely used in teaching English grammar: deductive and inductive. The effectiveness of two approaches is still in debate until today. Some teachers prefer to use the deductive approach, while some others prefer the inductive one. Which approach works well to university students: deductive, inductive, or combination of both? In this article, the writer will discuss about the two approaches, the pros and cons, and the example of an approach which combines both deductive and inductive approaches. The approach named story-based approach which will be more beneficial for the university students in the process of learning English grammar.